ANALISIS HASIL UASBN DITINJAU DARI STATUS FUNGSI GURU (GURU KELAS ATAU GURU BIDANG STUDI) DAN LATAR BELAKANG PENDIDIKAN GURU 1 ) - Ratna Nur Hidayati; Priyanti Ahadiani; Leonard Leonard (LPPM, 2010)
This study aimed to find influence functions of the status of teachers and educational background of teachers of elementary school students UASBN results in South Jakarta. This study is an ex post facto survey research, where esearchers only take the data that already exists within the respondents, so no need for additional treatment. Samples were taken with a purposive sampling technique, which means that the sample actually selected based on specific objectives, namely to find results UASBN of students taught by teachers with specific criteria based on the title of this research. The total number of samples as many as 323 people divided into four groups. Data were analyzed with descriptive statistics, data analysis, test requirements and test hypotheses with Two-Way ANOVA. Having proved to have normal distribution, then continued with the hypothesis test, which gives the result: 1) there is the influence of teachers' status on the yield UASBN function. 2) there was a background influence on the results UASBN teacher education. 3) there is interaction between functional status of teachers and educational background of teachers on the results UASBN. Based on the results of tests of hypotheses 3, then conducted further tests, with the result that the best UASBN values are in the group of students who were taught by teachers of relevant studies and science, while the lowest value at UASBN group of students who are taught by classroom teachers and science are not relevant. Keywords: classroom teachers, teachers' fields of study, mathematics, anova, uasbn, educational background.